Workshops of the seventh international brain-computer interface meeting: not getting lost in translation. Issue 3 (3rd July 2019) - Huggins, Jane E.; Guger, Christoph; Aarnoutse, Erik; Allison, Brendan; Anderson, Charles W.; Bedrick, Steven; Besio, Walter; Chavarriaga, Ricardo; Collinger, Jennifer L.; Do, An H.; Herff, Christian; Hohmann, Matthias; et al.
ABSTRACT: The Seventh International Brain-Computer Interface (BCI) Meeting was held May 21-25th, 2018 at the Asilomar Conference Grounds, Pacific Grove, California, United States. The interactive nature of this conference was embodied by 25 workshops covering topics in BCI (also called brain-machine interface) research. Workshops covered foundational topics such as hardware development and signal analysis algorithms, new and imaginative topics such as BCI for virtual reality and multi-brain BCIs, and translational topics such as clinical applications and ethical assumptions of BCI development. BCI research is expanding in the diversity of applications and populations for whom those applications are being developed. BCI applications are moving toward clinical readiness as researchers struggle with the practical considerations to make sure that BCI translational efforts will be successful. This paper summarizes each workshop, providing an overview of the topic of discussion, references for additional information, and identifying future issues for research and development that resulted from the interactions and discussion at the workshop.